IDENTIFICATION PATTERN OF WATER QUALITY REDUCTION OF BALANGAN RIVER USING INVERSE DISTANCE WEIGHTED METHOD IN BALANGAN REGENCY, SOUTH OF KALIMANTAN, INDONESIA - Dara Kusuma Wardhani; Novia Lusiana; Deni Agus Setyono (Journal of Environmental Engineering and Sustainable Technology, 2019)
The diversity of activities along the Balangan river causes waste disposal, which contributes to an increase in pollution load in the Balangan river. The purpose of this study is to predict the water quality conditions spatially using IDW method, and to determine the relation among distance and water quality status. In the whole location, the results showed that the pollution load capacity was exceeded, the levels of BOD5, COD, Sulfide, Iron, Manganese and Phosphate were parameters that had exceeded the quality standard. The pattern of water quality decreases in the downstream area, especially at BOD5 and COD levels. While the levels of TSS, Nitrate, Nitrite, Ammoniac, Iron, Manganese, and Detergent showed a temporary pattern of decline and showed an increase again. Phosphate levels showed a temporary increase and then there was a decrease again afterwards. Based on the sampling location the distance between the starting point and end point is 12 km, the prediction of the distribution of water quality using IDW shows that at a distance of 1-6 km shows a stable water quality pattern, a distance of 7-10 has improved water quality and 11-12 has decreased water quality.